Thoracic endovascular aortic repair under venoarterial extracorporeal membrane oxygenation for acute aortic dissection patients: a case report - Zhu, Leilei; Dong, Pingping; Du, Liwen; Xun, Kai; Liu, Peng; Lu, Xiaozhen; Shi, Yongwei (Frontiers in Cardiovascular Medicine, 2023)
Background Open repair and replacement of the diseased aorta is still the standard treatment for type A aortic dissection (TAAD) in most patients. In endovascular treatment alone, ensuring adequate blood supply to the brain while covering the dissection with a stent is difficult. Case presentation This study includes a 71-year-old male patient with type A aortic dissection presented at a recent follow-up examination after having undergone thoracic endovascular aortic repair (TEVAR) plus left subclavian artery chimney stent reconstruction for descending aortic dissection 5 years ago. Preoperative computed tomographic angiography, computed tomographic perfusion, and transcranial Doppler showed an intact cerebral arterial ring and good collateral circulation. We successfully performed an endovascular repair of the thoracic aorta with venoarterial extracorporeal membrane oxygenation (V-A ECMO) to protect the craniocerebral blood supply, greatly increase the safety of the operation, and ensure a good prognosis. Conclusion TEVAR under V-A ECMO protection is beneficial for patients with TAAD because of its minimal trauma, rapid recovery, few complications, and low mortality.